Diabetic Ketoacidosis Precipitated by COVID-19 in Patients Without Respiratory Symptoms: Case Reports - Meza, Jose L (Cureus, 2020)
Worse outcomes of coronavirus disease 2019 (COVID-19) have been documented in older patients with comorbidities, especially in those with diabetes mellitus (DM). However, the clinical picture and risk factors of COVID-19 in DM is still emerging. Here, we report four cases of severe COVID-19 patients with acute diabetic ketoacidosis (DKA) without respiratory symptoms, with viral and bacterial coinfection, and poor clinical outcomes. Higher monitoring of patients with DM and COVID-19 is advised, as well as rapid and accurate diagnostic tests and treatment.